Miller-Dieker syndrome resulting from rearrangement of a familial chromosome 17 inversion detected by fluorescence in situ hybridisation. Issue 1 (January 1996) - Kingston, H M; Ledbetter, D H; Tomlin, P I; Gaunt, K L
Abstract : We report a case of Miller-Dieker syndrome (MDS) owing to an unbalanced rearrangement of a familial pericentric inversion of chromosome 17 (inv(17) (p13.3q25.1)). In addition to lissencephaly and the facial features of MDS, the affected child had other congenital malformations consistent with distal 17q duplication. Initial cytogenetic analysis failed to show any abnormality and fluorescence in situ hybridisation (FISH) studies confirmed the 17p deletion in the proband and identified the chromosome 17 inversion in his mother. FISH studies were performed in other relatives and enabled first trimester prenatal diagnosis by chorionic villus sampling in a subsequent pregnancy of the proband's mother. These findings underline the value of FISH in the investigation of MDS families.